Microporous activated carbons from used coffee grounds for application to electric double‐layer capacitors. Issue 4 (July 2014) - Tashima, Daisuke; Hamasuna, Yoshihiro; Mishima, Daisuke; Kumagai, Seiji; Madden, John D. W.
<x xml:space="preserve">Abstract</x> Electrochemical double‐layer capacitors (EDLCs) are devices that store enormous amounts of charge electrostatically when a potential is applied between electrodes of very high surface area (typically made of porous carbon) and an electrolyte. Wider commercialization of this technology has been held back by the lack of ultralow‐cost electrode materials. We demonstrate that used coffee grounds can be processed to form low‐cost electrodes. The surface and electrochemical characteristics of microporous activated carbons from used coffee grounds (CGCs) were measured. First, optimal times and temperatures for carbonization and activation were identified on the basis of Brunauer–Emmett–Teller (BET) surface area, pore volume, and pore size distribution. Second, CGCs were used as polarized electrodes in EDLCs, whose capacitances were evaluated using cyclic voltammetry. The results show that carbonization for 1 h at 600 °C with a heating rate of 300 °C/h, followed by CO2 activation for 2 h at 1000 °C, affords the highest BET surface area (1867 m2/g) compared to other works. The produced CGCs have many micropores of less than 2 nm across, which contribute to the formation of an electric double layer. Capacitors made using these CGCs show the highest capacitance (103 F/g) in 0.8 M (C2H5)4NBF4/PC as an organic electrolyte, which is much higher than the ∼80 F/g typically used in organic‐electrolyte‐based commercial EDLCs, suggesting that coffee grounds are a useful electrode material. © 2014 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.